Porous blocky Fe2O3 (at) NiCoAl-LDH / CC flexible negative electrode and preparation method and application of porous blocky Fe2O3 (at) NiCoAl-LDH / CC flexible negative electrode
By in-situ growing porous bulk Fe2O3@NiCoAl-LDH core-shell structures on flexible carbon cloth, the problems of insufficient conductivity and mechanical flexibility of flexible electrode materials are solved, achieving electrochemical performance with high specific capacitance and long cycle life, which is suitable for flexible wearable devices.
Patent Information
- Application Number
- CN202511524440.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2025-12-09
AI Technical Summary
Existing technologies struggle to achieve effective composites of Fe2O3 and NiCoAl-LDH in flexible electrode materials, resulting in insufficient conductivity and mechanical flexibility, which fails to meet the requirements for high specific capacitance and long cycle life.
A porous, bulk Fe2O3@NiCoAl-LDH core-shell structure was grown in situ on flexible carbon cloth using a two-step hydrothermal method, avoiding the use of binders and directly constructing a composite material of Fe2O3 and NiCoAl-LDH on the carbon cloth, forming a continuous ionic/electron dual pathway.
It improves the utilization rate and conductivity of active materials, increases the specific surface area, enhances the flexibility and electrochemical performance of the electrode, exhibits high specific capacitance and excellent cycle stability, and is suitable for flexible wearable devices.
Smart Images

Figure CN121096790A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage materials technology, specifically relating to a porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode, its preparation method, and its application. Background Technology
[0002] With the increasing severity of environmental pollution from fossil fuel combustion, sustainable energy sources such as wind and solar power are gradually becoming the focus of future energy development. However, the intermittency and instability of these renewable energy sources limit their effectiveness in large-scale applications. Therefore, developing a safe, environmentally friendly, and efficient energy storage technology to achieve stable storage and power supply from renewable energy sources has become a current research focus. Electrochemical energy storage systems, due to their green, environmentally friendly, and efficient characteristics, are considered an effective way to solve this problem.
[0003] The core performance of supercapacitors lies in their electrode materials. Currently, electrode materials mainly include carbon-based double-layer materials (such as activated carbon and graphene) and pseudocapacitive materials (such as transition metal oxides and conductive polymers). While carbon-based materials offer good stability, they have relatively low specific capacitance. Pseudocapacitive materials, such as Fe2O3, while theoretically having high specific capacitance, low cost, and environmental friendliness, suffer from poor conductivity and large volume changes during charge and discharge, leading to poor rate performance and cycle stability. To address these issues, Fe2O3 is typically composited with conductive matrices (such as carbon materials) or with other active materials (such as layered double hydroxides, LDH) to construct synergistic composite structures.
[0004] Layered double hydroxides (LDHs) exhibit excellent pseudocapacitive properties due to their adjustable metal ion content in the layers, exchangeable anions between layers, and large specific surface area. Combining them with Fe₂O₃ holds promise for fully utilizing the advantages of both and improving overall electrochemical performance. However, traditional electrode fabrication processes typically require the use of insulating polymer binders to coat the active material onto the current collector. This not only introduces additional "dead volume," reducing the utilization rate of the active material, but also increases interfacial resistance. Furthermore, the coating is prone to cracking and peeling during bending, making it difficult to meet the requirements of flexible devices.
[0005] Publication No. CN109216036A discloses a method for preparing a flexible electrode of iron oxide nanowires supported on carbonized fiber cloth. This method simultaneously prepares a conductive carbon cloth substrate and Fe2O3 nanowires by activating the fiber cloth in an alkaline solution and then directly carbonizing it at high temperature. This technology confirms the feasibility of in-situ growth of Fe2O3 nanostructures on flexible carbon cloth, providing valuable insights for flexible electrode design. However, this technology is limited to a single Fe2O3 material system, and its specific capacitance and energy density are limited by the low conductivity of Fe2O3 itself, failing to address the application requirements of high-capacity energy storage.
[0006] Publication number CN117269273A discloses a carbon cloth self-supporting CoAl-LDHe@CoFe-PBA electrode and its preparation method. This technology demonstrates the possibility of constructing LDH-based composite materials on carbon cloth and has been successfully applied to the field of electrochemical sensing, showcasing the high activity advantage of LDH materials. However, the design and application goals of this composite material technology focus on sensing and detection, and its material system (CoAl-LDH and CoFe-PBA) and performance optimization direction differ significantly from the core requirements of high specific capacitance and long cycle life in the energy storage field. Furthermore, this technology also fails to solve the technical problem of synergistically improving energy storage performance by combining LDH with Fe2O3.
[0007] Existing technologies are either limited by the insufficient performance of single active materials (such as Fe2O3) or, although involving composite materials, their applications deviate from the energy storage field. More importantly, existing technologies have failed to provide an effective strategy for in-situ integration of Fe2O3 and multi-metallic LDH (especially NiCoAl-LDH) onto flexible carbon cloth in a core-shell structure, thereby simultaneously achieving high specific capacitance, excellent conductivity, and good mechanical flexibility.
[0008] Therefore, developing an in-situ grown electrode material with excellent flexibility and high electrochemical performance is of great significance for promoting the development of high-performance flexible supercapacitors. Summary of the Invention
[0009] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a porous bulk e2O3@NiCoAl-LDH / CC flexible anode material with a simple preparation process, no binder required, high specific capacitance, and excellent flexibility, as well as its preparation method and applications. To achieve the above objective, this invention is implemented through the following technical solutions: One of the objectives of this invention is to provide a method for preparing a porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode, which uses flexible carbon cloth as a substrate, on which Fe2O3 is grown in situ, and a NiCoAl-LDH layer is composited in situ on the surface of Fe2O3. The porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode has a core-shell structure.
[0010] Furthermore, a method for preparing a porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode includes the following steps: S1. Carbon cloth CC is immersed in a precursor solution containing iron salt and sodium sulfate. The precursor is generated on the carbon cloth through hydrothermal reaction. After annealing, Fe2O3 / CC composite material with porous blocky Fe2O3 is obtained. S2. Weigh out cobalt salt, nickel salt, and aluminum salt and dissolve them in deionized water, stirring to form a mixed solution A; weigh out urea and dissolve it in deionized water to form solution B; while stirring, use a peristaltic pump to slowly add solution B to solution A at a rate of 1 mL / min, and continue stirring to obtain a homogeneous mixed solution C. Immerse the Fe2O3 / CC composite material obtained in step S1 into the mixed solution C to carry out a secondary hydrothermal reaction, so that NiCoAl-LDH grows in situ on the Fe2O3 surface. After the reaction, wash and dry to obtain the porous blocky Fe2O3@NiCoAl-LDH / CC flexible negative electrode.
[0011] Furthermore, the iron salt mentioned in step S1 is FeCl3·6H2O.
[0012] Furthermore, in step S1, the temperature of the thermal reaction is 120°C and the time is 12 hours; the temperature of the annealing treatment is 400°C and the time is 2 hours.
[0013] Further, in the mixed solution described in step S2, Co 2+ The concentration of Ni is 0.06 mol / L. 2+ The concentration was 0.12 mol / L, Al 3+ The concentration of urea is 0.06 mol / L.
[0014] Furthermore, the feature is that the temperature of the secondary hydrothermal reaction in step S2 is 120°C and the time is 12 hours.
[0015] The second objective of this invention is to provide a Fe2O3@NiCoAl-LDH / CC flexible anode.
[0016] The third objective of this invention is to provide an application of Fe2O3@NiCoAl-LDH / CC flexible negative electrode in the working electrode of a capacitor.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The method for preparing porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode provided by this invention adopts a two-step hydrothermal method combined with annealing treatment, directly growing active materials in situ on flexible carbon cloth. This avoids the use of binders in traditional coating processes, eliminates the ineffective volume that does not contribute to capacity—the "dead volume"—generated by binders during the preparation process, and improves the utilization rate of active materials and the conductivity of the electrode. This preparation process is simple and does not require binders, and has strong potential for industrial production.
[0018] 2. This invention successfully constructed a core-shell structure with porous bulk Fe2O3 as the "core" and NiCoAl-LDH nanosheets as the "shell." This structure effectively increases the specific surface area of the electrode, provides abundant reactive sites, and promotes rapid diffusion of electrolyte ions and efficient electron transport. Fe2O3, acting as a supporting framework, suppresses the volume expansion and aggregation of LDH during charging and discharging, improving structural stability. LDH compensates for the insufficient conductivity of Fe2O3, providing a faster electron transport path. The combination of the two forms a continuous ion / electron dual pathway, significantly improving reaction kinetics and capacitance performance.
[0019] 3. The material provided by this invention uses flexible carbon cloth as a substrate, which makes the prepared electrode have good flexibility and mechanical strength, and can be bent and folded, making it suitable for flexible and wearable electronic devices.
[0020] 4. The flexible anode material provided by this invention has an areal capacitance of up to 0.86 F / cm² at a current density of 3 mA / cm², exhibiting excellent energy storage performance and cycle stability, which is far superior to single-component materials, and represents a significant advancement. Attached Figure Description
[0021] Figure 1 Scanning electron microscope image of the Fe2O3 / CC composite material prepared in Example 1; Figure 2 Scanning electron microscope image of the Fe2O3@NiCoAl-LDH / CC flexible anode prepared in Example 1; Figure 3 Transmission electron microscopy image of the Fe2O3@NiCoAl-LDH / CC flexible anode prepared in Example 2; Figure 4 Comparison of cyclic voltammetry curves for Fe2O3 / CC and Fe2O3@NiCoAl-LDH / CC flexible anodes; Figure 5 A comparison of the galvanostatic charge-discharge curves of Fe2O3 / CC and Fe2O3@NiCoAl-LDH / CC flexible anodes. Detailed Implementation
[0022] The present invention will be further described below with reference to preferred embodiments. The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges. These numerical ranges should be considered as specifically disclosed herein. Unless otherwise specified, all materials and reagents used in the following examples are commercially available. Unless otherwise specified, the experimental methods described in the following examples are conventional methods.
[0023] This embodiment provides a porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode, including the following steps: S1. Preparation of Fe2O3 / CC composite material: Weigh 4.067g FeCl3·6H2O and 2.135g Na2SO4, dissolve them in 60mL distilled water, and stir magnetically for 30 minutes to form a homogeneous precursor solution; immerse a 2cm×2cm carbon cloth, which has been ultrasonically cleaned with acetone and ethanol, into the above solution to ensure complete wetting; transfer the solution and carbon cloth together to a polytetrafluoroethylene-lined hydrothermal reaction vessel, and react in a 120℃ forced-air drying oven for 12 hours. After the reaction, allow it to cool naturally to room temperature, remove the carbon cloth, rinse it several times alternately with deionized water and anhydrous ethanol, and dry it in a 60℃ vacuum drying oven for 6 hours; place the dried sample in a tube furnace, and under nitrogen protection, heat it to 400℃ at a rate of 2℃ / min and hold it at that temperature for 2 hours for annealing treatment. After natural cooling, the Fe2O3 / CC composite material with Fe2O3 grown is obtained.
[0024] S2. Preparation of porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode: Weigh 1.045g Co(NO3)2·6H2O, 2.063g Ni(NO3)2·6H2O, and 1.341g... Al(NO3)3·9H2O was dissolved in 40 mL of deionized water and magnetically stirred for 30 minutes to form a mixed solution A. 2.142 g of urea was weighed and dissolved in 20 mL of deionized water to form solution B. Under stirring, solution B was slowly added dropwise to solution A at a rate of 1 mL / min using a peristaltic pump, and stirring was continued for 1 hour to obtain a homogeneous mixed solution C. The Fe2O3 / CC composite material prepared in step one was immersed in mixed solution C and then transferred to a hydrothermal reaction vessel and reacted at 120 °C for 12 hours. After the reaction was completed, the sample was naturally cooled, removed, and rinsed repeatedly with deionized water and anhydrous ethanol 5 times to remove impurities physically adsorbed on the surface. Finally, it was placed in a vacuum drying oven at 70 °C and dried for 24 hours to obtain the final product, a porous blocky Fe2O3@NiCoAl-LDH / CC flexible anode.
[0025] The Fe2O3 / CC composite material and the porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode prepared in the above embodiments were subjected to scanning electron microscopy and transmission electron microscopy tests. Scanning electron microscopy test results as follows Figure 1 and Figure 2 As shown; Figure 1 The image shows that Fe2O3 grows uniformly on the surface of the carbon fiber. Figure 2 The results show that NiCoAl-LDH was successfully grown in situ on the Fe2O3 surface, forming a more complex multi-layered structure and effectively increasing the specific surface area. Transmission electron microscopy test results as follows Figure 3 As shown: Figure 3 Transmission electron microscopy (TEM) image of a porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode. Figure 3 It can be seen that Fe2O3 grows on the surface of carbon cloth, forming a core-shell structure, in which Fe2O3 serves as the core and carbon cloth serves as the supporting substrate; Figure 3 The right figure shows the results of the Fe2O3@NiCoAl-LDH flexible anode composite. Fe2O3 grows in situ on the carbon cloth surface, and then composites with NiCoAl-LDH to form uniformly distributed granular LDH that grows again on the Fe2O3 surface. This result is compared with that obtained by scanning electron microscopy. Figure 1 This further confirms that the composite material was not only successfully synthesized, but also has a stable composite structure, indicating that there is good compatibility between Fe2O3 and NiCoAl-LDH.
[0026] The Fe2O3 / CC composite material and the porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode prepared in the above examples were subjected to electrochemical performance testing: cyclic voltammetry (CV) curve testing; the test voltage range was 1V to 0.5V, and the scan rate was 5 mV / s. The CV curve test results showed that the CV curve (red curve) of the porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode had a larger closed area and a higher current density, indicating that the composite material was superior to Fe2O3 / CC alone (black curve) in electrochemical performance; the larger CV curve area indicated that the composite material had a higher specific capacitance, which was due to the introduction of NiCoAl-LDH optimizing the ion transport path and improving the electron transfer efficiency, thereby significantly enhancing the electrochemical performance of the electrode material.
[0027] The Fe2O3 / CC composite material and the porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode prepared in the above embodiments were subjected to constant current charge-discharge tests: the charge-discharge voltage window was determined to be -1V to 0.4V by cyclic voltammetry, and the current density was set to 3mA / cm². The porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode and the Fe2O3 / CC composite material were used as working electrodes, with Hg / HgO as the reference electrode and Pt sheet as the counter electrode. The constant current charge-discharge curves of the two electrodes were measured. The cyclic method was "first constant current charging to 0.4V (stop charging after reaching this voltage), then constant current discharging to -1V (stop discharging after reaching this voltage)". The constant current charge-discharge curves were obtained after 5 charge-discharge activation cycles. The constant current charge-discharge test results are as follows. Figure 5 As shown, at a current density of 3 mA / cm², the discharge time of the porous bulk Fe₂O₃@NiCoAl-LDH / CC flexible anode (red curve) is significantly longer than that of Fe₂O₃ / CC (black curve). Calculations show that the areal capacitance of the porous bulk Fe₂O₃@NiCoAl-LDH / CC flexible anode is as high as 0.86 F / cm², demonstrating excellent energy storage performance.
[0028] The above embodiments are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Any equivalent structural or procedural modifications made based on the content of this specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A method for preparing a porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode, characterized in that, Using flexible carbon cloth as a substrate, Fe2O3 is grown in situ on it, and a NiCoAl-LDH layer is composited in situ on the surface of Fe2O3. The porous blocky Fe2O3@NiCoAl-LDH / CC flexible anode has a core-shell structure.
2. The method for preparing a porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode according to claim 1, characterized in that, Includes the following steps: S1. Carbon cloth CC is immersed in a precursor solution containing iron salt and sodium sulfate. The precursor is generated on the carbon cloth through hydrothermal reaction. After annealing, Fe2O3 / CC composite material with porous blocky Fe2O3 is obtained. S2. Weigh out the cobalt salt, nickel salt, and aluminum salt, dissolve them in deionized water, and stir to form a mixed solution A; weigh out... Urea, dissolved in deionized water, forms solution B; Under stirring, solution B is slowly added dropwise to solution A at a rate of 1 mL / min using a peristaltic pump. Stirring continues to obtain a homogeneous mixed solution C. The Fe2O3 / CC composite material obtained in step S1 is immersed in the mixed solution C to carry out a secondary hydrothermal reaction, so that NiCoAl-LDH grows in situ on the Fe2O3 surface. After the reaction, the material is washed and dried to obtain the porous blocky Fe2O3@NiCoAl-LDH / CC flexible anode.
3. The method for preparing a porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode according to claim 1, characterized in that, The iron salt mentioned in step S1 is FeCl3·6H2O.
4. The method for preparing a porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode according to claim 1, characterized in that, The temperature of the thermal reaction in step S1 is 120°C and the time is 12 hours; the temperature of the annealing treatment is 400°C and the time is 2 hours.
5. The method for preparing the porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode according to claim 1, characterized in that, In the mixed solution described in step S2, Co 2+ The concentration of Ni is 0.06 mol / L. 2+ The concentration was 0.12 mol / L, Al 3+ The concentration of urea is 0.06 mol / L.
6. The method for preparing the porous bulk Fe2O3@NiCoAl-LDH / CC flexible anode according to claim 1, characterized in that, The temperature of the secondary hydrothermal reaction in step S2 is 120°C, and the time is 12 hours.
7. A Fe2O3@NiCoAl-LDH / CC flexible anode prepared by the method described in any one of claims 1 to 6.
8. The application of the Fe2O3@NiCoAl-LDH / CC flexible negative electrode as described in claim 7 in the working electrode of a capacitor.
Citation Information
Patent Citations
A preparation method of a carbon fiber cloth loaded iron oxide nanowire flexible electrode
CN109216036A
Carbon cloth self-supporting CoAl-LDHe-coated CoFe-PBA electrode and preparation method and detection application thereof
CN117269273A